2021
DOI: 10.1002/pol.20210225
|View full text |Cite
|
Sign up to set email alerts
|

Organic dye‐based photoinitiating systems for visible‐light‐induced photopolymerization

Abstract: Even though many organic dyes have been reported as photoinitiators/photosensitizers for free radical polymerization in the literature, the design and development of novel photoinitiating systems based on organic dyes adaptable for visible light irradiation, for example, 405 nm LED and sunlight still remains challenging. Recently, major achievements in the development of high‐performance photoinitiating systems based on organic dyes as light‐harvesting compounds and their uses as photoinitiators for photopolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 171 publications
(274 reference statements)
0
52
0
2
Order By: Relevance
“…Upon irradiation with visible light these dyes photosensitize the decomposition of diphenyliodonium salts and active species formation. By using a combination of BODIPY and diphenyliodonium hexafluorophosphate, a nearly complete conversion to the desired polyvinyl polymer was observed after irradiation by a laser at 473 nm for a brief time [19,33]. It was also found that the addition of silanes to the photoinitiating system composed of BODIPY and diphenyliodonium salt increases the efficiency of the photopolymerization.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Upon irradiation with visible light these dyes photosensitize the decomposition of diphenyliodonium salts and active species formation. By using a combination of BODIPY and diphenyliodonium hexafluorophosphate, a nearly complete conversion to the desired polyvinyl polymer was observed after irradiation by a laser at 473 nm for a brief time [19,33]. It was also found that the addition of silanes to the photoinitiating system composed of BODIPY and diphenyliodonium salt increases the efficiency of the photopolymerization.…”
Section: Introductionmentioning
confidence: 94%
“…It is the chromophore and is often called the photoinitiator (PI) or the photosensitizer (PS). The second one could be an electron donor, an electron acceptor or a hydrogen donor [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…98 The basic advantages and disadvantages of squarine-based systems compared with other dyeing photoinitiating systems are summarized in Table 1. 39,86 According to the information in Table 1, both squaraines and other organic dyes can play the role of highly efficient photosensitizers. The photoinitiating ability of dyes depends on their chemical structure.…”
Section: Comparison Between Squaraine-based Photoinitiators and Other...mentioning
confidence: 99%
“…98 The basic advantages and disadvantages of squarine-based systems compared with other dyeing photoinitiating systems are summarized in Table 1. 39,86…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation